Prostitute Praising Represented by Male Novelists in Post-1998 Religious Society - Lelu Dina Apristia (POETIKA, 2022)
Prostitute praising is represented by Remy Sylado in novel titled Ca-Bau-Kan: Hanya Sebuah Dosa (1999)  and Arswendo Atmowiloto in novel titled Dewi Kawi (2008). Prostitute praising in the novels written by males in religious society in the midst of discourse about freedom of expression flowing in post-1998 era in Indonesia becomes problem of this research. Regarding the problem, this research aims to identify: (1) how prostitute praising is represented by males in their novel, (2) why male novelists produce such representations by applying Stuart Hall’s representation theory in relation to production of meaning through language and production of knowledge through discourse. The theory application reveals that male novelists represent prostitute praising in private and public domain which are mixed up and that there is relation between male and female in the domains siding with male as constructed by post-1998 discursive formation involving the state and religions to uphold masculine domination.